Design of Portable Clean Water Storage Facilities for Street Vendors - Alvian Fajar Setiawan; Nurul Fitriana Bahri (Journal of Industrial Product Design Research and Studies, 2022)
Culinary development in Indonesia is very rapid, it makes the proliferation of street food traders in big cities Indonesia one of them is pecel lele. The street food vendors must provide cutlery and drinking because many buyers eat the dishes in place, therefore there will be activities to wash cutlery and drink. These activities require clean water used for washing, generally the traders only bring a supply of clean water to wash only one or two drums it is very less. Moreover, the placement of drums on the floor making it difficult to remove the Clean Water. The water is used repeatedly so it is not efficient and effective. The purpose of this study is to create a design of clean water storage facilities for street vendors that are used during the activity of washing cutlery and drinking. The method used is qualitative to determine the needs of users by way of interviews and direct observation. The results of the design in the form of clean water storage facilities for street vendors with an emphasis on ergonomics aspects, so that users can be safer and more comfortable during activities. The results of this design is expected to be a reference and reference research and design in similar terms.